A 3D Bioprinted In Vitro Model of Pulmonary Artery Atresia to Evaluate Endothelial Cell Response to Microenvironment. Issue 20 (8th August 2021) - Tomov, Martin L.; Perez, Lilanni; Ning, Liqun; Chen, Huang; Jing, Bowen; Mingee, Andrew; Ibrahim, Sahar; Theus, Andrea S.; Kabboul, Gabriella; Do, Katherine; Bhamidipati, Sai Raviteja; Fischbach, Jordan; et al.
Abstract: Vascular atresia are often treated via transcatheter recanalization or surgical vascular anastomosis due to congenital malformations or coronary occlusions. The cellular response to vascular anastomosis or recanalization is, however, largely unknown and current techniques rely on restoration rather than optimization of flow into the atretic arteries. An improved understanding of cellular response post anastomosis may result in reduced restenosis. Here, an in vitro platform is used to model anastomosis in pulmonary arteries (PAs) and for procedural planning to reduce vascular restenosis. Bifurcated PAs are bioprinted within 3D hydrogel constructs to simulate a reestablished intervascular connection. The PA models are seeded with human endothelial cells and perfused at physiological flow rate to form endothelium. Particle image velocimetry and computational fluid dynamics modeling show close agreement in quantifying flow velocity and wall shear stress within the bioprinted arteries. These data are used to identify regions with greatest levels of shear stress alterations, prone to stenosis. Vascular geometry and flow hemodynamics significantly affect endothelial cell viability, proliferation, alignment, microcapillary formation, and metabolic bioprofiles. These integrated in vitro–in silico methods establish a unique platform to study complex cardiovascular diseases and can lead to direct clinical improvements in surgical planning for diseases of disturbed flow. Abstract : A 3D bioprinted in vitro model of pulmonary artery atresia is introduced as a research enabling platform to simulate reestablished intervascular connections. This hydrogel‐based endothelialized model of anastomosed arteries is used to investigate cell–microenvironmental interactions that can result in endothelial dysfunction and restenosis. Established platform allows conducting in‐depth analysis and developing enhanced clinical procedures to treat complex cardiovascular anomalies.